Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Komite Audit dan Leverage terhadap Integritas Laporan Keuangan: (Studi Empiris pada Perusahaan Manufaktur Sektor Food and Beverages di Bursa Efek Indonesia peiode 2021-2023) - Arini Izzatamillah; Rinny Meidiyustiani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to test and analyze the effect of Institutional Ownership, Managerial Ownership, Audit Committee and Leverage on Financial Statement Integrity in Food and Beverages Sector Manufacturing Companies on the Indonesia Stock Exchange for the 2021-2023 Period. The data used in this research is secondary data in the form of financial reports and annual reports of food and beverage sub-sector companies listed on the IDX from 2021-2023. The population in this study amounted to 20 company reports, with the sample determined through purposive sampling technique, and obtained a research sample of 18 companies. The analysis method used in this research is multiple linear regression using SPSS software version 25. The test results show that managerial ownership, audit committee have a positive influence on the integrity of financial statements, while institutional ownership and leverage have no influence on the integrity of financial statements.